2010
DOI: 10.1016/j.biomaterials.2010.02.052
|View full text |Cite
|
Sign up to set email alerts
|

Injectable PLGA based colloidal gels for zero-order dexamethasone release in cranial defects

Abstract: Bone fillers have emerged as an alternative to the invasive surgery often required to repair skeletal defects. Achieving controlled release from these materials is desired for accelerating healing. Here, oppositely-charged Poly (d,l-lactic-co-glycolic acid) (PLGA) nanoparticles were used to create a cohesive colloidal gel as an injectable drug-loaded filler to promote healing in bone defects. The colloid self-assembled through electrostatic forces resulting in a stable 3-D network that may be extruded or molde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
136
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(140 citation statements)
references
References 47 publications
(36 reference statements)
4
136
0
Order By: Relevance
“…These specifications will include issues such as load-bearing requirements, defect geometry (e.g., irregular vs. machined defects), bone architecture (e.g., cortical vs. cancellous), and vulnerable surrounding tissues (e.g., the spinal cord in vertebral fusion or brain tissue in calvarial repair). Existing design paradigms already used to support DBM particles, such as solid scaffolding or chemically cross-linked hydrogels 15 along with emerging design paradigms such as shear-responsive and self-assembling colloidal gels, [96][97][98][99][100] will likely yield an extensive array of application-specific bone regenerative scaffolds with EC ossification potential.…”
Section: Figmentioning
confidence: 99%
“…These specifications will include issues such as load-bearing requirements, defect geometry (e.g., irregular vs. machined defects), bone architecture (e.g., cortical vs. cancellous), and vulnerable surrounding tissues (e.g., the spinal cord in vertebral fusion or brain tissue in calvarial repair). Existing design paradigms already used to support DBM particles, such as solid scaffolding or chemically cross-linked hydrogels 15 along with emerging design paradigms such as shear-responsive and self-assembling colloidal gels, [96][97][98][99][100] will likely yield an extensive array of application-specific bone regenerative scaffolds with EC ossification potential.…”
Section: Figmentioning
confidence: 99%
“…Two recent studies have reported that 3D poly(DL-lactic-co-glycolic acid) (PLGA)-based scaffolds delivering dexamethasone stimulated in vivo bone regeneration in critical-sized defects after 4-8 weeks, compared to empty defects. 41,42 However, neither study demonstrated a clear benefit of dexamethasone delivery, since equivalent bone regeneration was seen with dexamethasone-free scaffolds in each case. 41,42 The effect on in vivo osteogenesis may depend on the method and temporal pattern of corticosteroid delivery.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…41,42 However, neither study demonstrated a clear benefit of dexamethasone delivery, since equivalent bone regeneration was seen with dexamethasone-free scaffolds in each case. 41,42 The effect on in vivo osteogenesis may depend on the method and temporal pattern of corticosteroid delivery. In a study of rat MSC-seeded titanium fiber meshes implanted in criticalsized rat cranial defects for 4 weeks, MSC preculture in media supplemented with dexamethasone for 4 days resulted in superior bone regeneration compared to MSCs cultured without dexamethasone.…”
Section: Corticosteroidsmentioning
confidence: 99%
“…For example, colloidal gels loaded with drugs have been studied as an injectable delivery system for use as an alternative to invasive surgery. Such gels are intended to accelerate the healing process and can be used as bone filler with shear thinning properties [7].…”
Section: Stokes Equationmentioning
confidence: 99%